2020
DOI: 10.1097/dad.0000000000001607
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Cancer Testis Antigens on Lentigo Maligna and Lentigo Maligna Melanoma

Abstract: The cancer/testis antigens (CTA) are a group of antigens expressed on germ cells of healthy testis and malignant tumors. We studied whether CTA are present on lentigo maligna (LM) and LM melanoma (LMM) samples. Immunohistochemical expression of a panel of CTA (MAGE-A1, A2- A3, NY-ESO-1, PRAME, SSX-2, and a MAGE-A antibody reactive with -A1, -A2, -A3, -A4, -A6, -A10, and -A12) was investigated in formalin-fixed paraffin-embedded samples from LMM (n = 20), LM (n = 8), chronically sun-exposed skin (n = 7), and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 9 publications
4
38
1
Order By: Relevance
“…Hence, immunohistochemical expression of PRAME may be useful to distinguish benign from malignant melanocytes. 14,15 In contrast to conventional nevi, we have occasionally observed NHP showing loss of HMB45 gradient and presence of HMB45 positive melanocytes in the deep dermis. To our knowledge, the use of PRAME immunohistochemistry has not yet been reported in NHP.…”
Section: Immunohistochemistrymentioning
confidence: 62%
See 1 more Smart Citation
“…Hence, immunohistochemical expression of PRAME may be useful to distinguish benign from malignant melanocytes. 14,15 In contrast to conventional nevi, we have occasionally observed NHP showing loss of HMB45 gradient and presence of HMB45 positive melanocytes in the deep dermis. To our knowledge, the use of PRAME immunohistochemistry has not yet been reported in NHP.…”
Section: Immunohistochemistrymentioning
confidence: 62%
“…Recent studies have shown that PRAME is diffusely expressed in the vast majority of non‐desmoplastic melanomas and PRAME expression is rare in melanocytic nevi. Hence, immunohistochemical expression of PRAME may be useful to distinguish benign from malignant melanocytes 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…A small series of LM ( n = 8) by Tio et al . showed that PRAME is expressed in 75% of LM, whereas the other members of the CTA family did not show expression in LM by IHC 9 . A second case–series of margin assessment in 10 cases of MIS by PRAME expression demonstrated that PRAME showed a good correlation with margin assessment, as determined by both H&E and SOX10 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Preferentially expressed antigen in melanoma (PRAME) is a cancer‐associated antigen that has been shown to be up‐regulated in melanoma, as well as acute leukaemia, neuroblastoma, breast carcinoma, renal cell carcinoma and multiple types of sarcoma 1–8 . Because PRAME is a member of the cancer testis antigen (CTA) family and shows absent to minimal expression in normal human tissues, with the exception of high expression in the testis and moderate expression in the ovary, adrenal gland and endometrium, it is an ideal target for immunotherapy 9 . Immunohistochemistry (IHC) for PRAME may also serve as an aid to diagnosis of difficult melanocytic lesions due to its specificity for malignant melanocytic lesions, with only rare staining in benign lesions (< 10% of cases) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…LM should be distinguished from atypical melanocytic hyperplasia (solar melanocytosis), which is often found in chronically sun-exposed skin of the face; this differentiation may be difficult, particularly in early LM. Immunostaining for the cancer testis antigen, PRAME, seems to be a promising tool to this effect (24).…”
Section: Introductionmentioning
confidence: 99%